Pengaruh Tingkat Pengangguran dan PDB Terhadap Tingkat Kemiskinan di Indonesia - Cindana, Hellen; Sa’adah, Nurus (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
This study aims to analyze the effect of unemployment rate and Gross Domestic Product (GDP) on poverty rate in Indonesia in the period 2000-2023. The method used is an associative quantitative approach with secondary data obtained from the World Bank. Data processing uses EViews through stationarity test, cointegration, classical assumptions, and Error Correction Model (ECM). The results of the study indicate that unemployment rate has a negative but insignificant effect on poverty, while GDP has a negative and significant effect. Simultaneously, unemployment and GDP have a significant effect on poverty rate in Indonesia. The coefficient of determination shows that both variables explain 50.46% of the variation in poverty rate. This finding confirms the importance of increasing GDP as the main strategy in reducing poverty rate in Indonesia.